Effects of synthesis technique on the physical properties of co-fe nanoparticles on cnts support - Ali, S. (Microscopy Society of Malaysia, 2013)
Bimetallic Co-Fe nanoparticles were synthesized via co-impregnation (IM), reversed microemulsion (RM) and strong electrostatic adsorption (SEA) methods. The synthesized nanocatalysts were characterized using scanning electron microscopy (SEM) and transmission electron microscopy (TEM) while the Fischer-Tropsch synthesis (FTS) reaction was studied in a fixed-bed microreactor. Results of microscopic analyses and N 2 gas adsorption studies show that the textural and morphological properties of the 70Co30Fe/CNTS catalysts were affected by the synthesis routes. The SEA method resulted in formation of metal oxide nanoparticles mostly on the outer walls of the CNTS. However, majority of the metal oxide nanoparticles resided in the inner walls of the CNTS when the co-impregnation and reversed microemulsion methods were applied. The average size of the metal oxide nanoparticles was found to be in the range of 2-7 nm. The performance of 70Co30Fe/CNTS catalysts in a Fischer- Tropsch synthesis (FTS) reaction was studied at 1 bar, 220Â°c and H 2 :CO ratio of 2:1. The highest CO conversion was 26.2 which was achieved using the Co-Fe/CNTs catalyst synthesized via the coimpregnation method whereas the lowest CO conversion was obtained using the catalyst prepared by the strong electrostatic method. The same trend was also observed in terms of selectivity values for the formation of C 5+ hydrocarbons. Â© 2019, Microscopy Society of Malaysia. All rights reserved.